PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK SULUTGO KANTOR PUSAT - Suprejo, Nanda Dewi Zafitri; Djawa, Djibrael (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2023)
The issues raised in writing this thesis are How Work Motivation on Employee Performance at PT. Bank Sulut Go, while the purpose of this study was to analyze